Perilaku Imitasi Pada Youtuber: Studi Pada Siswa SMPN 3 Martapura, Kabupaten Banjar - Mattiro, Syahlan; Widaty, Cucu; Renaldy, Muhammad (Lembaga Penelitian dan Pendidikan Mandala, 2022)
Social media affects all aspects of life, one of the most influential popular media platforms today is YouTube, which is easily accessible by teenagers. Therefore, the research objectives of this study (1) are to find the process of imitation in teenagers who watch Youtuber by students of SMP Negeri 3 Martapura. (2) Finding forms of imitation on Youtuber in the interactions that occur with students of SMPN 3 Martapura. The method in this study is a qualitative method. The data source was selected by Snowball Sampling with 8 students participating. The data collection used in the research are observation, interviews and documentation either directly or online. The results of the study show that (1) the process of imitation on Youtubers starts with easy accessibility. Like, the YouTube system itself and its social environment. Judging from the process which is divided into four stages, namely attentional, paying attention to Youtubers, retention which is storing what is watched, the formation of behavior where slowly imitation becomes behavior in the environment and is motivational, there is a motive for doing imitation behavior in the association (2) forms of communication in imitation are carried out. Copying behavior is seen from two forms of communication.The first is verbal, in the form of words either from mouth or in writing primarily (directly) or secondary (online).The second is non-verbal, namely in the form of symbols that can describe objects belonging to Youtubers in the form of physical, digital accessories or also additional gestures seen in the form of student social interaction.